2021
DOI: 10.3389/fnbeh.2021.761621
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Relaxation by Autonomous Sensory Meridian Response

Abstract: Background: Autonomous sensory meridian response (ASMR) is used by young people to induce relaxation and sleep and to reduce stress and anxiety; it comprises somatosensation caused by audiovisual stimuli (triggers) that lead to positive emotions. Auditory stimuli play the most important role among the triggers involved in ASMR and have been reported to be more triggering than visual stimuli. On the other hand, classical music is also known to have a relaxing effect. This is the first study to clarify the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…In both the ASMR and BB groups, subjective stress measured by questionnaires decreased to a similar extent. In the previous studies, the stress reduction effect between music and ASMR was the same, and produces a pleasant state of relaxation 9,16 . Mindfulness may involve spending specific time engaging in ASMR and therefore, www.nature.com/scientificreports/ when engaging in ASMR, the participant takes time to focus on the positive feelings triggered by the stimuli.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In both the ASMR and BB groups, subjective stress measured by questionnaires decreased to a similar extent. In the previous studies, the stress reduction effect between music and ASMR was the same, and produces a pleasant state of relaxation 9,16 . Mindfulness may involve spending specific time engaging in ASMR and therefore, www.nature.com/scientificreports/ when engaging in ASMR, the participant takes time to focus on the positive feelings triggered by the stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…The beta waves are associated with emotions 24 , and can also be increased in stressful situations 25 . In functional magnetic resonance imaging (fMRI) study, while classical music and ASMR display significant activation in similar areas, ASMR shows activation in more areas, primarily in the medial prefrontal cortex 16 . In an electroencephalogram study, ASMR experience was associated with increased alpha activity in the frontal www.nature.com/scientificreports/ sites 26 .…”
Section: Discussionmentioning
confidence: 99%
“…23 In functional magnetic resonance imaging (fMRI) study, while classical music and ASMR display signi cant activation in similar areas, ASMR shows activation in more areas, primarily in the medial prefrontal cortex. 14 In an electroencephalogram study, ASMR experience was associated with increased alpha activity in the frontal sites. 24 Considering the inhibitory effect of the alpha, the enhanced alpha may re ect a suppression of distractors and an active effort to disengage attention from the stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, the stress reduction effect between music and ASMR was the same, and produces a pleasant state of relaxation. 9,14 Mindfulness may involve spending speci c time engaging in ASMR and therefore, when engaging in ASMR, the participant takes time to focus on the positive feelings triggered by the stimuli. This behavior is very similar to mindfulness practices, which many studies have shown to improve both mental and physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this great popularity and the possible therapeutic potential of ASMR, a scientific evaluation of ASMR has hardly been conducted so far. First effects were recently demonstrated on aspects associated with mental health (inducing pleasant affect [ 1 3 ]; improving sleep quality [ 4 ]; inducing relaxation [ 3 , 5 ]; alleviating state anxiety [ 6 ]). Furthermore, initial evidence suggests that ASMR experience also triggers physiological responses.…”
Section: Introductionmentioning
confidence: 99%